Activating the Web as a Virtual and Dynamic Learning Environment - Fryer, Colin (Proceedings of the International Conference on Networked Learning, 2000)
In some subject areas the fusing of theory and practice can only be accomplished by demonstrating fundamental principles and their application via laboratory experiments. Although the benefits of underpinning the key conceptual and theoretical aspects with laboratory work have long been recognised, the practical and logistical problems associated with organising laboratories often results in students not fully engaging in the educational process. Unfortunately, many traditional laboratory experiments lose their impact if students are not fully prepared or appreciate the value of experimentation as an essential component in the learning process. The advent of the WWW provides a tremendous opportunity to address some of these issues through the provision of ’virtual’ laboratories where students are able to access the facilities at any time. However, the design of these information rich environments requires web authors to ’activate the Internet’ through the inclusion of a range of dynamic features if the on-line learning resources are not to be static and unchanging. These tools and technologies offer unlimited possibilities in the design of virtual worlds and the development of interactive Web sites. Through the use of a case study, this paper will discuss the design of a virtual laboratory and present a range of strategies for developing dynamic and active learning material for transmission over the Internet.